Antibacterial Activity of Ethanol Extract of Areca Vestiaria Leaves (Areca vestiaria) against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa bacteria - Wiranatika Jhonatan Sangkoy; Herny Simbala; Erladys Rumondor (UNIVERSITAS SAM RATULANGI, 2023)
WIRANATIKA SANGKOY. Antibacterial Activity of Ethanol Extract of Areca Vestiaria Leaves (Areca vestiaria) against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa bacteria. Under the guidance of HERNY EI SIMBALA as a leader and ERLADYS RUMONDOR as a member.One of the native plants of Indonesia that is widespread in several areas in Indonesia that has the potential to be developed in research testing antibacterial activity is the areca yaki leaf plant. This study aimed to determine the antibacterial activity of areca yaki (Areca vestiaria) leaves against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa at concentrations of 20%, 40%, and 60%. This research was conducted using the Kirby-Bauer method. From the results of this study, the data obtained that concentrations of 20%, 40%, and 60% of Staphylococcus aureus and Escherichia coli bacteria are concentrations that are included in the moderate group, while Pseudomonas aeruginosa at a concentration of 20% is included in the strong group and 40% and 60% are only included in the moderate group.